2014
DOI: 10.1021/jm5000112
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Chemical Functionalities of Indole-2-carboxamides To Improve Allosteric Parameters for the Cannabinoid Receptor 1 (CB1)

Abstract: 5-Chloro-3-ethyl-N-(4-(piperidin-1-yl)phenethyl)-1H-indole-2-carboxamide (1; ORG27569) is a prototypical allosteric modulator for the cannabinoid type 1 receptor (CB1). Here, we reveal key structural requirements of indole-2-carboxamides for allosteric modulation of CB1: a critical chain length at the C3-position, an electron withdrawing group at the C5-position, the length of the linker between the amide bond and the phenyl ring B, and the amino substituent on the phenyl ring B. These significantly impact the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 47 publications
2
68
0
Order By: Relevance
“…Compound 2 exhibited a similar response shown for comparison. 37,38 These results, and the enhancement in binding of the orthosteric agonist CP55,940, suggest that these compounds are PAMs and promote an active state of the receptor that may be biased to signal via β -arrestin-1 (at least for ERK1/2 phosphorylation) and not G protein.…”
Section: Resultsmentioning
confidence: 97%
“…Compound 2 exhibited a similar response shown for comparison. 37,38 These results, and the enhancement in binding of the orthosteric agonist CP55,940, suggest that these compounds are PAMs and promote an active state of the receptor that may be biased to signal via β -arrestin-1 (at least for ERK1/2 phosphorylation) and not G protein.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have focused on 4-substitutions on this phenyl ring, particularly 4-amino groups such as piperidinyl and dimethylamino. 25-27 Here we introduced a number of other amino groups at several positions. The activity of the piperidine ring-opened series (compounds 16 - 19 ) was found to be sensitive to the length of the alkyl substituent.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it appears that a flexible alkyl linker is important to CB1 activity, which is in agreement with Khurana et al who showed that the ethylene moiety was the optimal linker. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate future proteomic study of allosteric sites on the CB1 receptor, we designed and synthesized several photoactivatable affinity ligands based on 1 and several other robust CB1 allosteric modulators (i.e. 7–9 , Figure 2) reported previously [3133]. Compounds 7 [31], 8 [33] and 9 [32, 35] have been demonstrated to have either comparable or improved allosteric effects to 1 [3133].…”
Section: Introductionmentioning
confidence: 99%